1983
DOI: 10.1126/science.6823560
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to a Malignant Lymphoma in Chickens Is Mapped to Subregion of Major Histocompatibility ( B ) Complex

Abstract: A genetic recombinant within the major histocompatibility (B) complex of the chicken has revealed the chromosomal subregion effecting resistance to Marek's disease--a malignant lymphoma induced by a herpesvirus. The recombinant, BF21-G19, occurred spontaneously among the progeny of a male heterozygous for resistant BF21-G21 and susceptible BF19-G19 haplotypes. Exposure to Marek's disease of families segregating for the recombinant showed that this new F-G arrangement conferred a level of resistance equivalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
91
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(93 citation statements)
references
References 15 publications
2
91
0
Order By: Relevance
“…Antigen presenting molecules encoded by different BF2 alleles bind quite different classes of peptides (7-10) and thereby likely selectively influence adaptive immune responses to antigen, but the gene or genes that provide MHC-linked resistance to virally induced tumors in chickens are not known. Recently, the crossover breakpoint in the recombinant haplotype originally used to map MD resistance to the MHC-B subregion marked by BF2 was localized, which revealed that 27 genes lie within the region between the crossover breakpoint and the BF2 locus (4,11). Thus, it is now evident that many genes are candidates for providing the long noted MHC-B haplotype-linked resistance to MD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Antigen presenting molecules encoded by different BF2 alleles bind quite different classes of peptides (7-10) and thereby likely selectively influence adaptive immune responses to antigen, but the gene or genes that provide MHC-linked resistance to virally induced tumors in chickens are not known. Recently, the crossover breakpoint in the recombinant haplotype originally used to map MD resistance to the MHC-B subregion marked by BF2 was localized, which revealed that 27 genes lie within the region between the crossover breakpoint and the BF2 locus (4,11). Thus, it is now evident that many genes are candidates for providing the long noted MHC-B haplotype-linked resistance to MD.…”
mentioning
confidence: 99%
“…In the chicken, the MHC-B region has an exceptionally strong role in genetic resistance to Marek's disease (MD) caused by gallid herpesvirus-2 (GaHV-2) and to Rous sarcoma virus (RSV)-induced tumors (1,2). Resistance to these diseases maps to the MHC-B subregion marked by a highly expressed classical MHC class I gene (3)(4)(5)(6). It has been suggested that strong MHC-B disease associations are apparent as the result of alleles at this single locus for classical class I antigen presentation, BF2, contributing to immune responses either independently or in concert with closely-linked transporter associated with antigenprocessing (TAP) genes (6,7).…”
mentioning
confidence: 99%
“…However, background genes (including non-immune system genes) appear to have an important role in MHC-dependent parasite resistance where a particular MHC haplotype may be associated with either resistance or susceptibility to a given pathogen depending on the genetic background of the host (Apanius et al 1997;Medina & North 1998). Hence, it is still a contentious issue to what extent the results from inbred laboratory strains can be extrapolated to outbred populations (Apanius et al 1997), where evidence is solely based on correlative data with no control for effects of non-MHC genes (Briles et al 1983;Hill et al 1991;Thursz et al 1997;Paterson et al 1998;Carrington et al 1999;Langefors et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…T cells recognize and bind the Mhc-foreign antigen complex, thereby initiating a chain of events to stimulate the adaptive immune response to fight infection. It is now well appreciated that Mhc polymorphism plays a central role in resistance to infectious and autoimmune disease in birds and mammals (Briles et al 1983;Kaufman and Wallny 1996;Hill 1999). Soon after the proximate molecular functions of Mhc genes were elucidated, it was also recognized that, by nature of their role in self-nonself recognition and high polymorphism, Mhc genes could play a role in kin recognition and mate choice (Yamazaki et al 1976).…”
mentioning
confidence: 99%